(untitled) (Research Announcements "Heritage BG", 2025)
The paper presents the main features of the EpiDoc-compliant XML template according to which ancient inscriptions in Greek and Latin from the lands of today’s Bulgaria are encoded and then indexed and displayed in the browsable and searchable databases TELAMON and TITVLI References: Botusharova, L. (1959). Obrochni relefi na Apolon ot Trakiya. – Annuaire du Musée national archéologique Plovdiv, 3, 145-153. Besevliev, V. (1964). Spätgriechische und spätlateinische Inschriften aus Bulgarien. Berlin. Dimitrov, D. (1931). Zur Geschichte der Stadt Augusta Traiana. – Bulletin de la Société Historique Sofia, 11-12, 61-69. Elliott, T., Bodard, G., Mylonas, E., Stoyanova, S., Tupman, C., Vanderbilt, S., et al. (2007-2022). EpiDoc Guidelines: Ancient documents in TEI XML (Version 9.6). https://epidoc.stoa.org/gl/latest/ (accessed 23.07.2024). Flanders, J., Roueché, C. (2006). Introduction To Markup For Epigraphers. https://blog.stoa.org/archives/4084 (accessed 06.04.2024). Gerov, B. (1989). Inscriptiones Latinae in Bulgaria repertae. Serdicae. Heřmánková, P., Horster, M., Prag, J. (2022). Digital Epigraphy in 2022: A Report from the Scoping Survey of the FAIR Epigraphy Project (v1.0.0). https://doi.org/10.5281/zenodo.6610696 (accessed 07.04.2024). Iliev, D., Boeva, E. (2023). From stone to screen: The Telamon database of ancient inscriptions in Greek from Bulgaria. – AIP Conference Proceedings, 2939/1. https://doi.org/10.1063/5.0178753. Mihailov, G. (1956-1995). Inscriptiones Graecae in Bulgaria repertae. Serdicae, Voll. I-V. Reynolds, J., Roueché, C., Bodard, G. (2007). Inscriptions of Aphrodisias. http://insaph.kcl.ac.uk/iaph2007 (accessed 06.04.2024). Sharankov, N. (2016). Notes on the Greek Inscriptions from Bulgaria. – Studia Classica Serdicensia 5, 305-361. Sharankov, N. (2024). Antichnite nadpisi na Dionisopol. Sofia University Press 2024. Sopracasa, A., Filosa, M. (2020). Encoding Byzantine Seals: SigiDoc. In: Atti del IX Convegno Annuale AIUCD. La svolta inevitabile: sfide e prospettive per l’Informatica Umanistica. (eds. C. Marras, M. Passarotti, G. Franzini, E. Litta). Milano, 240-245. Tasovac, T., Romary, L., Toth-Czifra, E., Ackermann, R. C., Alves, D., et al. (2023). The Role of Research Infrastructures in the Research Assessment Reform: A DARIAH Position Paper. ffhal-04136772f. Online at: https://hal.science/hal-04136772 (accessed 20.07.2024). The TEI Consortium (eds.) (2024). TEIP5: Guidelines for Electronic Text Encoding and Interchange. [Version 4.8.0.]. http://www.tei-c.org/Guidelines/P5/ (accessed 23.07.2024).